Effects of a single dose 20 mg tadalafil on resistive index value of prostate zones - Şahinkanat, Tayfun; Efe, Erkan; Ekerbiçer, Hasan Çetin; Küçükdurmaz, Faruk (The European Research Journal, 2018)
Objectives: Although there are several studies addressing the efficacy of phosphodiesterase type 5 inhibitors for the management of benign prostatic hyperplasia-lower urinary tract symptoms (BPH-LUTS), unfortunately, there is a lack of high evidence data to support their effect at the prostate level. The existing studies suggested that resistive index (RI) could be used as a hemodynamic parameter to measure the severity of benign prostatic hyperplasia and intraprostatic pressure or bladder outlet obstruction. The aim of this study was to evaluate the effect of a single dose 20 mg tadalafil on resistive index value in prostate zones to evaluate the mechanism of action of phosphodiesterase type 5-inhibitors at the prostate level. Methods: Twenty consecutive patients aged between 54-67 years with BPH-LUTS [International Prostate Symptom Score ≥ 12] and erectile dysfunction [five-item International Index of Erectile Function (IIEF) questionnaire < 22] underwent RI measurement in prostate transitional zone (TZ) and peripheral zone (PZ) using transrectal power Doppler ultrasonography baseline and within 16 hours after the administration of 20 mg tadalafil. The primary study end point is the change in prostate TZ RI values. Results: The mean baseline total prostate scores and peak urinary flow were 16.2 ± 4.34 (range: 12-26) and 10.45 ml/s (range: 7-13 ml/s), respectively. The mean baseline total IIEF was 12.8 ± 4.22 (range: 6-20). The mean TZ RI at baseline and after tadalafil administration were 0.4985 and 0.5497, respectively (p = 0.232). No statistically significant differences for RI changes between baseline and after the administration of a single dose 20 mg tadalafil were observed in the prostatic zones. Conclusion: A single dose 20 mg tadalafil showed no impact on prostate TZ RI.